2020
DOI: 10.1016/j.mehy.2020.110147
|View full text |Cite
|
Sign up to set email alerts
|

Are night shift workers at an increased risk for COVID-19?

Abstract: Recent data has revealed an association between coronavirus disease-19 (COVID-19) incidence and seasonally regulated androgen sensitivity. This potential relationship between SARS-CoV-2 infection and clock genes, coupled with previously reported effects of night shift work on health, leads us to hypothesize that night shift workers may be at an increased physiological risk of coronavirus disease-19 (COVID-19). Shift work, especially night shift work, has long been associated with several chronic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…Alongside other risk factors (e.g. health-related behaviours [ 15 ], psychological stress and genetic predisposition), this may be associated with a ‘cytokine storm’ [ 22 , 29 , 30 ] contributing to the increased odds of severe COVID-19 we observed in shift-workers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alongside other risk factors (e.g. health-related behaviours [ 15 ], psychological stress and genetic predisposition), this may be associated with a ‘cytokine storm’ [ 22 , 29 , 30 ] contributing to the increased odds of severe COVID-19 we observed in shift-workers.…”
Section: Discussionmentioning
confidence: 98%
“…Shift workers are more likely to have disturbed sleep and variable sleep patterns [ 21 ] leading to disruption of the circadian rhythm. This has been hypothesised to increase the odds of COVID-19 in night shift workers [ 22 ], but is evident even if the shift pattern does not include night work, likely due to sleep disruption in relation to circadian rhythms [ 21 ], which may persist in the years following cessation of shift work [ 23 ]. Recent data have suggested that sleep disruption and high variability in sleep timing are associated with the odds of testing positive for COVID-19 and development of severe infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For COVID-19, collecting samples in the morning (when most people routinely use the bathroom) may help capture a larger viral load. However, some suggest that larger flows in the morning could result in a more diluted signal ( WRF 2020 ), and morning sampling might also overlook certain underrepresented populations, such as shift workers, who may be more susceptible to COVID-19 and exacerbating chronic conditions ( Lim et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside other risk factors (e.g. lifestyle factors, psychological stress and genetic predisposition), this may be associated with a ‘cytokine storm’ 22,28,29 contributing to the increased risk of severe COVID-19 we observed in shift-workers.…”
Section: Discussionmentioning
confidence: 89%